Modernization and Development: Impact on Health Care Decision-Making in Uganda - Singh, D.; Earnest, Jaya; Lample, M. (Taylor & Francis Group LLC, 2013)
Uganda has faced numerous challenges over the past 50 years from overcoming political conflict and civil unrest, to rapid population growth, to combating the HIV epidemic and ever-growing health needs. Women in Uganda have had a major role to play in the health of families and communities. The researchers' purpose in this study, undertaken in rural Uganda, was to a) identify a people-centered definition of development, b) compare it to the process of modernization, and c) investigate how these processes have changed the role women play in decision-making, in areas directly and indirectly related to their health and that of their families. Twenty-two men and women participated in focus group discussion and completed questionnaires. Based on our analysis of discussions it appears that both modernization and development have impacted health positively and negatively. Key themes distilled from interviews included that modernization has led to the breakdown of families; increased maternal responsibility for children; diminished land and economic resources; and an erosion of cultural values and practices that had previously provided stability for the society. In terms of development, women play an increasing role in decision-making processes in the household and are gaining increasing respect for their expertise in a number of areas, notably health care. We propose a movement of grassroots discourse on modernization. Development, and its effect on health, is necessary if the positive aspects of Ugandan culture and those of similar emerging societies are not to be lost (International Covenant on Economic, Social and Cultural Rights, 1966).